Non-timber Values and the Optimal Forest Rotation: An Application to the Southern Forest of Tasmania - CAMPBELL, HARRY F.; JENNINGS, SARAH M. (The Economic record, 2004)
The present paper examines the optimal use of a site containing standing timber, taking account of both timber and non‐timber values. Using a site in the southern forest of Tasmania for illustrative purposes, it calculates the relationships between age of stand, extent of timber and non‐timber values and optimal cutting age. It finds that, for a stand with moderate potential environmental benefits, there is a period of its life during which it is optimal to log. This segment narrows, and eventually disappears, as potential environmental benefits increase.